EFEKTIVITAS DIGITALISASI : PENGGUNAAN E-LEARNING SEBAGAI MEDIA PEMBELAJARAN DALAM PENDIDIKAN - Elzati, Risa Wara (STAI Tuanku Tambusai, 2024)
The aim of this research is to determine the effectiveness of digitalization in the use of e-learning learning media in education. This type of research is experimental research with a Completely Randomized Design model. The sample in this research consisted of 60 students who were divided into two research classes. The first research class carried out statistics lecture activities using YouTube media. The second research class carried out statistics lecture activities using Microsoft Teams media. Data analysis uses the average value of pretest and posttest learning outcomes in each research class and compares the average learning outcomes using YouTube and Microsoft Teams media. Data was obtained from respondents by giving written test questions (essays) which had been tested for validity and reliability, both learning before using e-learning media (pretest) and learning after using e-learning (posttest). The research results show that the average learning outcomes of students who use YouTube e-learning learning media and Microsoft Teams e-learning learning media show a significant difference. Student learning outcomes in statistics courses, both those using YouTube media and those using Microsoft Teams media, do not show any differences. which is significant so that the effectiveness of using the two e-learning learning media for education has a positive influence.